Hardening liquid formula and hardened film prepared from hardening liquid formula
The hardening liquid formulation with specific polyurethane acrylates and photoinitiators addresses the challenges of adhesion, hardness, and curl on PMMA substrates, achieving improved anti-glare and anti-reflective performance for display devices.
Patent Information
- Application Number
- CN202411795100.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-14
AI Technical Summary
Current technologies face challenges in achieving good adhesion, hardness, low reflectance, and low curl of hardening layers on PMMA substrates, which are essential for effective anti-glare and anti-reflective coatings in display devices.
A specific hardening liquid formulation comprising 24.0-30.0% double-functional polyurethane acrylate, 10.0-15.0% hexa-functional polyurethane acrylate, and specific photoinitiators, applied in a UV-curable process to form a hardening layer with enhanced adhesion, hardness, and reduced reflectance and curl on PMMA substrates.
The hardening layer demonstrates excellent adhesion, hardness, and low reflectance and curl characteristics, addressing the limitations of existing technologies by forming a high-performance anti-glare and anti-reflective coating.
Smart Images

Figure BDA0005176438020000121 
Figure BDA0005176438020000131 
Figure BDA0005176438020000141
Abstract
Description
Technical Field
[0001] The invention relates to a hardening coating liquid formula and a hardening film made from the same, which has good adhesion to a PMMA substrate and takes into account hardness, low reflectivity and low warpage. Background Art
[0002] In modern home environments, living room TVs are the main entertainment devices, and their display effects are crucial to the user's viewing experience. However, the impact of reflected light is often overlooked. When natural light or indoor lighting shines on the TV screen, the reflected light will interfere with the screen surface, resulting in reduced image clarity and color distortion. Especially on sunny days, reflected light may blur details on the screen, affecting the audience's viewing comfort. At the same time, the presence of reflected light may also make the black areas on the screen gray, reduce contrast, and thus reduce the overall visual experience. Therefore, in the design and layout of the TV, it is necessary to consider how to effectively reduce the impact of reflected light on the display effect.
[0003] The prior art uses an anti-glare optical film added to the outer protective substrate of the outer polarizer of the display device to reduce the visual effect caused by the reflection of the external ambient light. Among them, the anti-glare film used to improve the above phenomenon mainly includes a substrate layer and an anti-glare coating layer. The substrate serves as a carrier, and the anti-glare coating layered thereon provides a scattering effect. With the help of the microscopic rough surface formed by particles of different sizes in the anti-glare coating, the incident ambient light can be evenly diffused on the surface, thereby reducing the glare on the screen surface.
[0004] The substrates used as the outer protective film of the outer polarizer generally include triacetate (TAC), super phase retardation film (SRF), cycloolefin (COP) and polymethyl methacrylate (PMMA). In recent years, with the increase in the size of liquid crystal displays, TAC is used as the substrate of the outer polarizing protective film. Due to its high water vapor permeability, the liquid crystal panel is prone to deformation after absorbing moisture during sea transportation, causing light leakage at the edges or corners. Although SRF has a low water vapor permeability, it is easy to have an abnormal rainbow appearance at a large viewing angle in a high color gamut panel, so PMMA, which has balanced properties such as water vapor permeability and low phase, is used as an alternative to the substrate of the outer polarizing protective film. However, due to the current equipment conditions, the PMMA substrate can only be coated with a primer layer (Primer layer) on one side for use in subsequent bonding with PVA. The side used for coating the hardening layer or anti-glare layer has not been treated in any way.
[0005] CN200810027254.7 discloses a UV curing hardening liquid, which is composed by weight of 5-40wt% of high-functional aliphatic polyurethane acrylate, 5-15wt% of cyclic monofunctional acrylate monomer, 5-10wt% of difunctional aliphatic polyurethane acrylate, 5-25wt% of difunctional acrylate, 1-5wt% of photoinitiator, 20-60wt% of diluent, and 0.01-1wt% of auxiliary agent.
[0006] CN201210305573.6 discloses an antistatic hardening film, comprising a film substrate and a UV-curable antistatic hardening coating layer coated thereon, wherein the UV-curable antistatic hardening coating layer is made of the following components by weight percentage after UV curing: 20-40% multifunctional polyurethane acrylate, 50-70% alcohol and / or ether reagents, 5-10% UV-curable active monomers, 1-20% organic surfactant type antistatic agent, 1-10% photoinitiator, and 0.1-0.5% coating additives.
[0007] CN201510683233.0 discloses an anti-fouling and anti-UV coating composition, a hardened film and a preparation method. The components and weight proportions of the anti-fouling and anti-UV coating composition are: 15 to 35 parts of multi-functional acrylate prepolymer, 15 to 30 parts of UV active monomer, 2 to 8 parts of photoinitiator, 0.1 to 0.5 parts of leveling agent, 2 to 6 parts of ultraviolet absorber, 5 to 30 parts of silica dispersion, and 30 to 50 parts of organic solvent.
[0008] CN202311840557.1 discloses an anti-glare hard coating liquid comprising: 15-30 parts by weight of polyurethane acrylate, 1-10 parts by weight of polyester acrylate, 1-5 parts by weight of photoinitiator, 60-85 parts by weight of organic solvent, 0.1-1 parts by weight of organic micron particles, 0.1-1 parts by weight of inorganic nanoparticles, 0.1-1 parts by weight of dispersant and 0.1-1 parts by weight of leveling agent; the acid value of polyester acrylate is ≥4mgKOH / g, the molecular weight of polyurethane acrylate is less than that of polyester acrylate, and the organic solvent contains 10-30 parts by weight of ketone solvent.
[0009] CN202311823306.2 discloses a high-adhesion UV coating composition for corona PET and a method for preparing its hardened coating. The coating composition includes the following components: 20%-60% amino-modified polyurethane acrylic oligomer; 0.4-1.2% leveling agent; 0.5-1.2% antistatic agent; 1-4% photoinitiator; and 40-75% solvent.
[0010] Although the prior art attempts to solve the problem of coating adhesion on PMMA substrates by hard coating liquid, there is currently no suitable technical solution that can improve the adhesion of the coating on the PMMA substrate while taking into account the need for the coating to have low reflectivity and warping, which is the basis for further development of anti-glare and anti-reflective coatings and optical films. Summary of the invention
[0011] In order to solve the problems of poor adhesion between the hardened coating and the PMMA substrate in the anti-glare film and the hardness, low reflectivity and low warping, the present invention provides a hardening liquid formula for the PMMA substrate and an optical film made therefrom, which has good adhesion to the PMMA substrate and the hardness, low reflectivity and low warping.
[0012] In order to solve the above technical problems, the present invention adopts the following technical solutions.
[0013] The present invention first provides a hardening liquid for PMMA substrate, which is composed of: 24.0-30.0% of difunctional polyurethane acrylate oligomer, 10.0-15.0% of hexafunctional polyurethane acrylate oligomer, 0-16.0% of trimethylolpropane triacrylate, 0.2-0.5% of photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.75-1.5% of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.05-0.25% of polyether modified silicone, 0.05-0.25% of antistatic agent, and the rest of solvent, and the percentages are all mass percentages. The hardening liquid has good adhesion to the PMMA substrate, and takes into account hardness, low reflectivity and low warpage.
[0014] The hardening liquid is coated on the PMMA substrate to form a hardened layer, the adhesion of the hardened layer is 5B, the hardness is not less than H, the reflectivity is less than 5%, and the warpage is less than 4.0 mm.
[0015] Furthermore, the content of the difunctional polyurethane acrylate oligomer is 26.0-29.0%, or 26.5%, 27.0%, 27.5%, 28.0%, 28.5%, or 29.0%.
[0016] Furthermore, the content of the hexafunctional polyurethane acrylate oligomer is 10.5-14.5%, or 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%.
[0017] Furthermore, the content of the trimethylolpropane triacrylate is 1.0-15.0%, or 2.0%, 5.0%, 7.0%, 10.0%, or 12.0%.
[0018] Furthermore, the content of the photoinitiator 1-hydroxycyclohexyl phenyl ketone (ie, photoinitiator 184) is 0.25-0.45%, or 0.30%, 0.35%, or 0.40%.
[0019] Furthermore, the content of the photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (ie, photoinitiator TPO) is 0.8-1.4%, or 0.9%, 1.0%, or 1.2%.
[0020] Furthermore, the content of the leveling agent is 0.10-0.20%, or 0.15%.
[0021] Furthermore, the content of the antistatic agent is 0.10-0.20%, or 0.15%.
[0022] Furthermore, the polyether-modified silicone has a modified partial segment and an unmodified partial segment, the modified partial segment is an incompatible segment, the unmodified partial segment is a segment with limited compatibility, and the modified partial segment includes a polyethylene oxide and a polypropylene oxide structure, which has good compatibility, feel, leveling ability, foam stability and recoatability.
[0023] Furthermore, the antistatic agent is selected from one or a combination of at least two of alkyl sulfonates, sulfates, phosphoric acid derivatives, higher fatty acid salts, carboxylates and polymeric ionic antistatic agents.
[0024] Furthermore, the antistatic agent is preferably an ionic antistatic agent. Furthermore, the ionic antistatic agent is an anionic antistatic agent, mainly including alkyl sulfonates, alkyl sulfates, alkyl phosphates, alkylphenol polyoxyethylene ether sulfates, etc., specifically bis(trifluoromethylsulfonyl)imide salts, etc.
[0025] Furthermore, the solvent is one or a combination of at least two of ethyl acetate (EA), butyl acetate (BA), methyl isobutyl ketone (MIBK), etc.
[0026] Furthermore, the solvent is preferably methyl isobutyl ketone.
[0027] Meanwhile, tetrahydrofuran acrylate (TFHA) and 1,6-hexanediol diacrylate (HDDA) are not used in the hardening solution of the present invention.
[0028] The present invention also provides an optical film, which includes a PMMA substrate layer and a hardened layer, wherein the hardened layer is formed by coating a hardening liquid on the PMMA substrate, wherein the hardening liquid is the hardening liquid of the present invention, and the thickness of the substrate is 30-100 μm; the thickness of the hardened layer is 1.0-5.0 μm.
[0029] Furthermore, the thickness of the substrate is preferably 35-95 μm, or 40 μm, 60 μm, 80 μm, or 90 μm.
[0030] Furthermore, the thickness of the hardened layer is preferably 1.5-4.5 μm, or 2.0 μm, 2.5 μm, 3.0 μm, or 3.5 μm.
[0031] The hardening liquid is coated on the PMMA substrate to form a hardened layer, the adhesion of the hardened layer is 5B, the hardness is not less than H, the reflectivity is less than 5%, and the warpage is less than 4.0 mm.
[0032] Furthermore, the reflectivity is lower than 4.5%, or lower than 4.2%.
[0033] Furthermore, the warpage is less than 3.0 mm, or less than 2.0 mm, or less than 1.0 mm.
[0034] The present invention also provides a method for preparing an optical film, wherein the optical film comprises a PMMA substrate layer and a hardened layer, wherein the hardened layer is formed by coating a hardening liquid on the PMMA substrate, wherein the hardening liquid is the hardening liquid of the present invention, and the preparation of the hardened coating specifically comprises the following steps:
[0035] (1) preparing a hardening liquid, weighing components of the hardening liquid, mixing, stirring, and forming the hardening liquid;
[0036] (2) coating, coating the hardening liquid on the surface of the PMMA substrate;
[0037] (3) drying, drying the sample after coating the hardening liquid;
[0038] (4) Curing: UV curing the dried sample to form a hardened coating.
[0039] Furthermore, in step (1), other components of the hardening liquid except the solvent are weighed as the main resin, added into the solvent, and stirred thoroughly.
[0040] Furthermore, in step (2), a wire rod is used for coating.
[0041] Furthermore, in step (3), the drying is performed by placing the sample in an oven at 80-85° C. and drying for 3-5 minutes.
[0042] Furthermore, in step (4), the UV curing is performed by placing the sample in a tunnel-type UV curing oven and setting the power at 100-150 mW / cm 2 , Set the line speed at 5-10m / min, and control the UV cumulative energy at 150-300mJ / cm 2 Complete light curing.
[0043] Furthermore, in step (4), the UV curing is to place the sample in a tunnel-type UV curing oven and set the power to 110 mW / cm 2 、120mW / cm 2 、130mW / cm 2 、140mW / cm 2 , set the line speed at 6m / min, 7m / min, 8m / min, 9m / min, and control the UV cumulative energy to 180mJ / cm 2 、200mJ / cm 2 、230mJ / cm 2 、250mJ / cm 2 、260mJ / cm 2 、280mJ / cm 2 .
[0044] The present invention also provides an application of a hardening liquid in improving the performance of an optical film, wherein the optical film comprises a PMMA substrate layer and a hardening layer, wherein the hardening layer is formed by coating a hardening liquid on the PMMA substrate, wherein the hardening liquid is the hardening liquid of the present invention, and wherein the performance comprises adhesion, hardness, warping and reflectivity between the PMMA substrate and the hardening layer.
[0045] The hardening liquid is coated on the PMMA substrate to form a hardened layer, the adhesion of the hardened layer is 5B, the hardness is not less than H, the reflectivity is less than 5%, and the warpage is less than 4.0 mm.
[0046] Furthermore, the reflectivity is lower than 4.5%, or lower than 4.2%.
[0047] Furthermore, the warpage is less than 3.0 mm, or less than 2.0 mm, or less than 1.0 mm.
[0048] When the proportion of each component in the hardening liquid is controlled within the above range, the hardening liquid can be polymerized by free radicals under a UV light source to form a hardening coating with high hardness and excellent adhesion on the surface of the substrate.
[0049] Compared with the prior art, the basic curing liquid formula provided by the present invention and the hardened film made thereof can form hydrogen bonds with the carbonyl group in the PMMA substrate by means of a large number of hydrogen bond coordination sites (amide bonds) in the polyurethane acrylate oligomer. At the same time, the adhesion area between the coating and the substrate is increased by the erosion of the PMMA substrate by solvents such as ethyl acetate and methyl isobutyl ketone. And by controlling the ratio of multifunctional polyurethane acrylate oligomers in the coating, the shrinkage rate of the coating after UV curing is reduced. Based on the above reasons, the hardened layer formed by the curing liquid provided by the present invention has good adhesion to the PMMA substrate, and takes into account good hardness, low warping and reflectivity, which is the basis for further developing anti-glare and low reflection functions on the basis of this hardened coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 Schematic diagram of the structure of the hardened film.
[0051] 01: Base material layer, 02: Hardening layer
[0052] Figure 2 This is a photo of a hardened film coated with a hardened coating on a PMMA substrate, as in Example 1.
[0053] Figure 3 is a photograph of a hardened film coated with an adhesion 5B hardening coating on a PMMA substrate, such as Example 14.
[0054] Figure 4 This is a photo of a hardened film coated with an adhesion 3B hardening coating on a PMMA substrate, such as Comparative Example 5. DETAILED DESCRIPTION
[0055] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the preferred embodiments of the present invention are described in detail with reference to the drawings as follows:
[0056] like Figure 1 As shown, the hardened film provided by the present invention specifically includes a substrate 01 and a hardened layer 02 stacked on the substrate.
[0057] The present invention provides a process for making a hardened film, which is completed according to the following steps.
[0058] A light-transmitting substrate (polymethyl methacrylate film with a thickness of 40 μm) was prepared, and a curing liquid composition as shown below was coated on one side of the light-transmitting substrate. A wire rod with a suitable mesh size was selected to coat the film on a coating machine to obtain a uniform wet film.
[0059] Next, the film was placed in an oven at 85°C for 3 minutes to evaporate the organic solvent in the wet film.
[0060] Finally, use a cumulative 300-500mJ / cm2 The ultraviolet energy causes the film layer to be further UV-cured to obtain a hardened layer with a thickness of about 3-5 μm, thereby preparing the hardened films of the embodiments and comparative examples.
[0061] The key properties of the hardened film provided by the present invention are tested according to the following test standards:
[0062] Transmittance and haze test: According to the "JISK7105-1981" standard, i.e. "Test method for optical properties of plastics", the transmittance and haze of the hardened film in the visible light band are tested; the testing equipment is Nippon Denshoku NDH 7000.
[0063] Pencil hardness test: According to the "JIS K5400-1990" standard, i.e. "Paint film adhesion test method", the pencil hardness of the hardened layer is tested using a Mitsubishi pencil test.
[0064] Adhesion test of hardened layer: According to GB 1720-1979, i.e., Paint Film Adhesion Test Method, the adhesion between hardened coating and substrate is tested and recorded. 5B means that the coating has not fallen off, 4B to 1B respectively represent different degrees of coating falling off, and 0B means that the coating has completely fallen off.
[0065] Test of abrasion resistance: According to the standard "HG / T 4303-2012", i.e. "Test Method for Wear Resistance of Surface Hardened Polyester Film", the wear resistance of the hardened layer was tested, using 0000# steel wool and 250gf / cm2 load, and the test equipment was Jinliang Industrial's wear tester A20-339. The wear resistance of the hardened film can be judged by testing the number of wear tests when scratches are produced on the surface of the film.
[0066] Solvent resistance test: According to GB / T 23989-2009, i.e., Determination Method of Solvent Resistance of Coatings by Wiping. Use absorbent cotton soaked in solvent to wipe the corresponding coating back and forth once, let it stand for 1 hour, wipe it with distilled water and dry it, and observe whether the coating surface appearance changes. No change is judged as excellent; slight change is judged as good; obvious change or whitening is judged as poor.
[0067] Reflectivity test: The test was conducted in accordance with the ASTM F1252-2016 standard, i.e., Standard Test Method for Measurement of Optical Reflectivity of Transparent Materials. The test was completed using Konica Minolta's CM3600A. The non-test surface was covered with black tape (Bachuan).
[0068] Experimental materials: Difunctional polyurethane acrylate oligomer was provided by Sartomer, tetrafunctional polyurethane acrylate oligomer was provided by Changxing Chemical Company, hexafunctional polyurethane acrylate oligomer was provided by Guangzhou Runao Chemical Company, acrylate tetrahydrofuran ester, 1,6-hexanediol diacrylate, and trimethylolpropane triacrylate were all provided by Changxing Chemical, photoinitiators TPO and 184 were provided by Hubei Gurun Technology Co., Ltd.; ionic antistatic agent bistrifluoromethylsulfonyl imide salt was provided by Jiangsu Guotai Chaowei New Materials Co., Ltd., and polyether-modified silicone was provided by BYK Chemical.
[0069] The raw material composition for preparing the hardened film and the performance test of the hardened film in the examples and comparative examples of the present application are described in detail below.
[0070] Example 1
[0071] Weigh 24.0% of difunctional polyurethane acrylate oligomer (component A, the same below), 10.0% of hexafunctional polyurethane acrylate oligomer (component C, the same below), 16.0% of trimethylolpropane triacrylate (TMOTA), 0.2% of photoinitiator 1-hydroxycyclohexyl phenyl ketone (TPO), 0.75% of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (184), 0.15% of polyether modified silicone (component D, the same below), and 0.15% of bistrifluoromethylsulfonyl imide salt ionic antistatic agent (component E, the same below) as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 50%.
[0072] A wire rod of appropriate size was selected, and the hardening solution obtained in the above embodiment 1 was coated on a 40 μm PMMA substrate. The hardening solution was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0073] Example 2
[0074] Weigh 24.0% component A, 10.0% component C, 16.0% trimethylolpropane triacrylate, 0.5% photoinitiator TPO, 1.5% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 50%.
[0075] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 2 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0076] Example 3
[0077] Weigh 24.0% component A, 10.0% component C, 16.0% trimethylolpropane triacrylate, 0.5% photoinitiator TPO, 1.5% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 50%.
[0078] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 3 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0079] Example 4
[0080] Weigh 24.0% component A, 10.0% component C, 16.0% trimethylolpropane triacrylate, 0.5% photoinitiator TPO, 1.5% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 50%.
[0081] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 4 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0082] Example 5
[0083] 30.0% component A, 5.0% tetrafunctional polyurethane acrylate oligomer (component B, the same below), 5.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E were weighed separately as the main resin. The main resin was added to the remaining amount of ethyl acetate solvent and stirred thoroughly to form a hardening solution with a solid content of about 40%.
[0084] A wire rod of appropriate size was selected, and the hardening solution obtained in the above embodiment 5 was coated on a 40 μm PMMA substrate. The hardening solution was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0085] Example 6
[0086] Weigh 30.0% component A, 10.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0087] A wire rod of appropriate size was selected, and the hardening solution obtained in the above Example 6 was coated on a 40 μm PMMA substrate. The hardening solution was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0088] Example 7
[0089] Weigh 30.0% component A, 10.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining butyl acetate solvent and stir thoroughly to form a hardening solution with a solid content of about 40%.
[0090] A wire rod of appropriate size was selected, and the hardening solution obtained in the above embodiment 7 was coated on a 40 μm PMMA substrate. The hardening solution was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0091] Example 8
[0092] Weigh 30.0% component A, 10.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining amount of methyl isobutyl ketone solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0093] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 8 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0094] Example 9
[0095] Weigh 25.0% component A, 15.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0096] A wire rod of appropriate size was selected, and the hardening solution prepared in Example 9 was coated on a 40 μm PMMA substrate. The hardening solution was dried and UV cured to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0097] Example 10
[0098] Weigh 25.0% component A, 15.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining butyl acetate solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0099] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 10 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0100] Embodiment 11
[0101] Weigh 25.0% component A, 15.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining amount of methyl isobutyl ketone solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0102] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 11 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0103] Example 12
[0104] Weigh 28.0% component A, 12.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0105] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 12 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0106] Example 13
[0107] Weigh 28.0% component A, 12.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining butyl acetate solvent and stir thoroughly to form a hardening solution with a solid content of about 40%.
[0108] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 13 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0109] Embodiment 14
[0110] Weigh 28.0% component A, 12.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining amount of methyl isobutyl ketone solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0111] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above embodiment 22 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0112] In order to further evaluate and compare the effects of the type of acrylate monomer and its functionality on improving the hardness of the hardened coating and the adhesion to the PMMA substrate, the present invention designs the following comparative examples for illustration.
[0113] Comparative Example 1
[0114] Weigh 24.0% of component A, 10.0% of component C, 16.0% of tetrahydrofuran acrylate (TFHA), 0.2% of photoinitiator TPO, 0.75% of photoinitiator 184, 0.15% of component D, and 0.15% of component E as the main resin. Add the above main resin into the remaining amount of ethyl acetate solvent and stir well to form a hardening solution with a solid content of about 50%.
[0115] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above comparative example 1 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0116] Comparative Example 2
[0117] Considering the increase in the number of monomers in the hardening solution, the proportion of photoinitiator was increased to evaluate the influence on the performance of the hardened coating. Weigh 24.0% component A, 10.0% component C, 16.0% TFHA, 0.5% photoinitiator TPO, 1.5% photoinitiator 184, 0.15% component D, and 0.15% component E as the main resin. Add the above main resin to the remaining ethyl acetate solvent and stir thoroughly to form a hardening solution with a solid content of about 50%.
[0118] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above comparative example 2 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film is shown in Table 1.
[0119] Comparative Example 3
[0120] Similar to the implementation schemes of Comparative Examples 1 and 2, the functionality of the acrylic monomer in the hardening solution is increased to 2, and the influence of the increase in monomer functionality on improving the hardness and adhesion of the coating is evaluated. Weigh 24.0% of component A, 10.0% of component C, 16.0% of 1,6-hexanediol diacrylate (HDDA), 0.2% of photoinitiator TPO, 0.75% of photoinitiator 184, 0.15% of component D, and 0.15% of component E as the main resin. Add the above main resin to the remaining ethyl acetate solvent and stir thoroughly to form a hardening solution with a solid content of about 50%.
[0121] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above comparative example 3 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0122] Comparative Example 4
[0123] Based on Comparative Example 3, the effect of increasing the proportion of photoinitiator added on improving the hardness and adhesion of the coating was further evaluated. 24.0% of component A, 10.0% of component C, 16.0% of HDDA, 0.5% of photoinitiator TPO, 1.5% of photoinitiator 184, 0.15% of component D, and 0.15% of component E were weighed as the main resin. The above main resin was added to the remaining ethyl acetate solvent and stirred thoroughly to form a hardening liquid with a solid content of about 50%.
[0124] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above comparative example 4 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0125] In order to further evaluate the influence of oligomer functionality and addition ratio on coating hardness and adhesion, the following comparison is designed to illustrate.
[0126] Comparative Example 5
[0127] Weigh 20.0% component B, 20.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0128] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above comparative example 5 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0129] Combining Example 12 with Comparative Example 5, it can be seen that for the content of difunctional and hexafunctional oligomers, as the difunctional ratio increases, although the adhesion is good, the hardness will slowly decrease, and as the hexafunctional ratio increases, there is a risk of decreased adhesion.
[0130] Comparative Example 6
[0131] Weigh 10.0% component A, 10.0% component B, 20.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0132] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above comparative example 6 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0133] Comparative Example 7
[0134] Weigh 20.0% component A, 10.0% component B, 10.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0135] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above comparative example 7 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0136] Comparative Example 8
[0137] Weigh 20.0% component A, 20.0% component C, 0.2% photoinitiator TPO, 0.75% photoinitiator 184, 0.15% component D, and 0.15% component E respectively as the main resin. Add the above main resin into the remaining ethyl acetate solvent and stir well to form a hardening liquid with a solid content of about 40%.
[0138] A wire rod of appropriate size was selected, and the hardening liquid obtained in the above comparative example 8 was coated on a 40 μm PMMA substrate. The hardening liquid was dried and UV cured in sequence to obtain a hardened layer with a thickness of about 1.0-2.0 μm. The performance test data of the prepared hardened film are shown in Tables 1 and 2.
[0139] Table 1. Component table of Examples 1-14 and Comparative Examples 1-8 (content of each component is in mass percentage).
[0140]
[0141]
[0142] Description: Component A represents: difunctional polyurethane acrylate oligomer; component B represents tetrafunctional polyurethane acrylate oligomer; component C represents hexafunctional polyurethane acrylate oligomer; component D represents polyether modified silicone; component E represents antistatic agent.
[0143] Table 2: Summary of test results of various embodiments and comparative examples.
[0144] Transmittance (%) Haze(%) Adhesion hardness Wear resistance Ethanol resistance MIBK resistant Example 1 92.01 1.30 5B H 500 times excellent good Example 2 92.18 1.38 5B H 500 times excellent good Example 3 92.20 1.29 5B H 500 times excellent good Example 4 92.15 1.41 5B H 500 times excellent good Example 5 92.35 1.34 5B H 500 times excellent good Example 6 92.27 1.42 5B H 500 times excellent good Example 7 92.07 1.38 5B H 500 times excellent good Example 8 92.08 1.24 5B H 500 times excellent excellent Example 9 92.28 1.22 5B H 500 times excellent good Example 10 92.19 1.27 5B H 500 times excellent good Embodiment 11 92.33 1.24 5B H 500 times excellent excellent Example 12 92.24 1.27 5B H 500 times excellent good Example 13 92.28 1.33 5B H 500 times excellent good Embodiment 14 92.31 1.35 5B H 500 times excellent excellent Comparative Example 1 92.27 1.33 5B F 300 times Difference Difference Comparative Example 2 92.17 1.34 5B F 300 times Difference Difference Comparative Example 3 92.22 1.41 5B F 300 times Difference Difference Comparative Example 4 92.19 1.40 5B F 300 times Difference Difference Comparative Example 5 92.29 1.34 3B H 350 times excellent good Comparative Example 6 92.07 1.39 3B H 350 times excellent good Comparative Example 7 92.25 1.40 4B H 350 times excellent good Comparative Example 8 92.14 1.41 4B H 350 times excellent good
[0145] Embodiment 15
[0146] Furthermore, in order to improve the wear resistance of the hardened film, the formula of Example 15 of the present invention is based on the formula of Example 14, and an additional 5.0% mass fraction of a photocurable anti-fingerprint AF additive is added to the hardening liquid. Different wire rods are selected, and the hardening liquid is coated on a 40μm PMMA substrate. The hardening liquid is dried and UV-cured in turn to obtain a hardened layer with a thickness of about 1.0-2.0μm. The detailed formula composition and the performance test data of the prepared hardened film are shown in Tables 3 and 4.
[0147] Example 16
[0148] Furthermore, in order to improve the wear resistance of the hardened film, the formula of the embodiment of the present invention is based on the formula of Example 14, and an additional 5.0% mass fraction of the hardening liquid is added to the light-curable anti-fingerprint AF additive, and different wire rods are selected to coat the hardening liquid on a 40μm PMMA substrate. The hardening liquid is dried and UV-cured in turn to obtain a hardened layer with a thickness of about 2.0-3.0μm. The detailed formula composition and the performance test data of the prepared hardened film are shown in Tables 3 and 4.
[0149] Embodiment 17
[0150] Furthermore, in order to improve the hardness and wear resistance of the hardened film, the formula of the embodiment of the present invention is based on the formula of Example 14, and an additional 5.0% mass fraction of a photocurable AF additive is added. Different wire rods are selected, and the hardening liquid is coated on a 40μm PMMA substrate. The hardening liquid is dried and UV-cured in turn to obtain a hardened layer with a thickness of about 3.0-4.0μm. The detailed formula composition and the performance test data of the prepared hardened film are shown in Tables 3 and 4.
[0151] Embodiment 18
[0152] Furthermore, in order to improve the hardness and wear resistance of the hardened film, the formula of the embodiment of the present invention is based on the formula of Example 14, and an additional 5.0% mass fraction of a photocurable AF additive is added. Different wire rods are selected, and the hardening liquid is coated on a 40μm PMMA substrate. The hardening liquid is dried and UV-cured in turn to obtain a hardened layer with a thickness of about 4.0-5.0μm. The detailed formula composition and the performance test data of the prepared hardened film are shown in Tables 3 and 4.
[0153] Table 3. Component table of Examples 14-18 (content of each component is in mass percentage).
[0154]
[0155] Table 4. Summary of test results of Examples 14-18.
[0156]
[0157] From the test results of the above embodiments and comparative examples, it can be concluded that the present invention provides a hardening liquid with excellent adhesion to a PMMA substrate and a hardened film with low reflectivity made therefrom. Among them, the hardened films provided by Examples 1-14 have good adhesion, wear resistance, and solvent resistance (ethanol, MIBK, etc.). In particular, Examples 15-18 have higher hardness and wear resistance, while taking into account lower warping and reflectivity.
[0158] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.
Claims
1. A hardening solution for a PMMA substrate, comprising: 24.0-30.0% of difunctional polyurethane acrylate oligomer, 10.0-15.0% of hexafunctional polyurethane acrylate oligomer, 0-16.0% of trimethylolpropane triacrylate, 0.2-0.5% of photoinitiator 1-hydroxycyclohexyl phenyl ketone, 0.75-1.5% of photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 0.05-0.25% of polyether modified silicone, 0.05-0.25% of antistatic agent, and the balance is solvent, and the percentages are all mass percentages.
2. The hardening liquid according to claim 1, characterized in that: The content of the difunctional polyurethane acrylate oligomer is 26.0-29.0%, or 26.5%, 27.0%, 27.5%, 28.0%, 28.5%, 29.0%.
3. The hardening solution according to any one of claims 1-2, characterized in that: The content of the hexafunctional polyurethane acrylate oligomer is 10.5-14.5%, or 11.0%, 11.5%, 12.0%, 12.5%, 13.0%, 13.5%, 14.0%, 14.5%.
4. The hardening solution according to any one of claims 1 to 3, characterized in that: The content of the trimethylolpropane triacrylate is 1.0-15.0%, or 2.0%, 5.0%, 7.0%, 10.0%, 12.0%.
5. The hardening liquid according to any one of claims 1 to 4, characterized in that: The content of the photoinitiator 1-hydroxycyclohexyl phenyl ketone (ie, photoinitiator 184) is 0.25-0.45%, or 0.30%, 0.35%, or 0.40%.
6. The hardening liquid according to any one of claims 1 to 5, characterized in that: The content of the photoinitiator 2,4,6-trimethylbenzoyl-diphenylphosphine oxide (ie, photoinitiator TPO) is 0.8-1.4%, or 0.9%, 1.0%, or 1.2%.
7. The hardening solution according to any one of claims 1 to 6, characterized in that: The content of the leveling agent is 0.10-0.20%, or 0.15%.
8. The hardening liquid according to any one of claims 1 to 7, characterized in that: The antistatic agent is selected from one or a combination of at least two of alkyl sulfonates, sulfates, phosphoric acid derivatives, higher fatty acid salts, carboxylates and polymeric ionic antistatic agents.
9. An optical film, comprising a PMMA substrate layer and a hardened layer, wherein the hardened layer is formed by coating a hardening liquid on the PMMA substrate, wherein the hardening liquid is the hardening liquid of any one of claims 1 to 8, the thickness of the substrate is 30-100 μm; and the thickness of the hardened layer is 1.0-5.0 μm.
10. The optical film according to claim 9, characterized in that: The thickness of the substrate is preferably 35-95 μm, or 40 μm, 60 μm, 80 μm, or 90 μm.
11. The optical film according to claim 9, characterized in that: The thickness of the hardened layer is preferably 1.5-4.5 μm, or 2.0 μm, 2.5 μm, 3.0 μm, or 3.5 μm.
12. The optical film according to claim 9, characterized in that: The hardening liquid is coated on the PMMA substrate to form a hardened layer, the adhesion of the hardened layer is 5B, the hardness is not less than H, the reflectivity is less than 5%, and the warpage is less than 4.0 mm.
13. The optical film according to claim 9, characterized in that: The reflectivity is lower than 4.5%, or lower than 4.2%.
14. The optical film according to claim 9, characterized in that: The warpage is less than 3.0 mm, or less than 2.0 mm, or less than 1.0 mm.
15. A method for preparing an optical film according to any one of claims 9 to 14, wherein the optical film comprises a PMMA substrate layer and a hardened layer, wherein the hardened layer is formed by coating a hardening liquid on the PMMA substrate, wherein the hardening liquid is the hardening liquid according to any one of claims 1 to 8, and the preparation of the hardened coating layer specifically comprises the following steps: (1) preparing a hardening liquid, weighing components of the hardening liquid, mixing, stirring, and forming the hardening liquid; (2) coating, coating the hardening liquid on the surface of the PMMA substrate; (3) drying, drying the sample after coating the hardening liquid; (4) Curing: UV curing the dried sample to form a hardened coating.
16. The method for preparing an optical film according to claim 15, characterized in that: In step (3), the drying is to place the sample in an oven at 80-85° C. and dry it for 3-5 minutes.
17. The method for preparing an optical film according to any one of claims 15-16, characterized in that: In step (4), the UV curing is to place the sample in a tunnel-type UV curing oven and set the power at 100-150 mW / cm 2 , Set the line speed at 5-10m / min, and control the UV cumulative energy at 150-300mJ / cm 2 Complete light curing.
18. Use of the hardening liquid of any one of claims 1-8 in improving the performance of an optical film, wherein the optical film comprises a PMMA substrate layer and a hardening layer, wherein the hardening layer is formed by coating the hardening liquid on the PMMA substrate, and the performance is adhesion, hardness, warping and reflectivity between the PMMA substrate and the hardening layer.
19. The use according to claim 18, characterized in that The hardening liquid is coated on the PMMA substrate to form a hardened layer, the adhesion of the hardened layer is 5B, the hardness is not less than H, the reflectivity is less than 5%, and the warpage is less than 4.0 mm.
20. The use according to claim 19, characterized in that The reflectivity is lower than 4.5%, or lower than 4.2%, and the warpage is lower than 3.0 mm, or lower than 2.0 mm, or lower than 1.0 mm.
Citation Information
Patent Citations
Ultraviolet light curing hardening liquid
CN101255289A
Anti-static hardened film
CN102786875A
Anti-fouling and anti-UV (ultraviolet) coating composition, hard coating film and preparation method
CN105273586A
High-adhesive-force UV coating composition applied to corona PET and preparation method of hardened coating of high-adhesive-force UV coating composition
CN117777840A
Anti-dazzle hard coating liquid, anti-dazzle hard coating film and image display device
CN117801665A
Cited By
Laser coating for laser film as well as preparation method and application of laser coating
CN121471773A